THE TYPES AND ORE-CONTROLLING FACTORS OF LOCALIZATION OF ORE-GOLD MINERALIZATION IN DONBASS - Kurylo, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This paper deals with detailed characteristic of the basic types of ore-gold mineralization in Donetsk region, distribution and localization of the ore-controlling factors.